A Nameless Bride of Death: Jephthah’s Daughter in American Jewish Women’s Poetry - Koplowitz-Breier, Anat (Open theology, 2020)
In the Hebrew Bible, Jephthah’s daughter has neither name nor heir. The biblical account (Judg. 11:30-40) is somber—a daughter due to be sacrificed because of her father’s rash vow. The theme has inspired numerous midrashim and over five hundred artistic works since the Renaissance. Traditionally barred from studying the Jewish canon as women, many Jewish feminists are now adopting the midrashicpoetry tradition as a way of vivifying the female characters in the Hebrew Bible. The five on which this article centers focus on Jephthah’s daughter, letting her tell her (side of the) story and imputing feelings and emotions to her. Although not giving her a name, they hereby commemorate her existence—and stake a claim for their own presence, autonomy, and active participation in tradition and society as Jewish women.